Optimization of anode usage in electroplating process by using response surface methodology - Begum S.; Tarlochan F.; Sambasivam K. (2023)
Electroplating is a process of depositing a layer of metal onto another base metal using the electrodeposition technique, where an acid is used as a medium of transferring the desired metal onto the base metal. During electroplating some amount of anodes are wasted and burnt and ended up not being used on the end product. A series of experiments with various input parameters were carried out in order to identify the best possible setting which would result in minimum anode usage. The experiments were designed using two level full factorial design. It was observed from factorial analysis that all the input variables like the porosity of anodes in anode basket, concentration of electrolyte and applied voltage have pronounced effect on the anode usage; however, the most significant influence was from porosity. The usage of the anodes was much less as the porosity due to the arrangement of anode in anode basket decreased. The interactive affects of the input variables such as the porosity and the voltage, and the porosity and the concentration were also prominent. The optimum operating conditions were identified by response optimizer plot and were verified experimentally. Both the analytical and experimental results indicated that anode usage could be reduced by 6.12% from that of the current practice. Hence it can be concluded that the operating variables in electroplating industry have significant effect on anode usage. (2012) Trans Tech Publications, Switzerland.